Programme standards: medical and health sciences - Mamat, Nik Mazlan; Arshad, Fatimah; Abdullah, Habibah; Hing, Hiang Lian; Kamaruddin, Kamaria; Osman, Khairul; Abdullah, Mohd Yunus; Ismail, Noor; Chau Dam, Pim; Jamaluddin, Saiful Adli; Kamso, Siti Arbi (Malaysian Qualification Agency, 2013)
This document, The Programme Standards: Medical and Health Sciences (the Programme Standards), contains benchmarked statements pertaining to the field of medical and health sciences. The complex multidisciplinary nature of medical and health science requires a sound, research-informed, scientific education. Graduates must acquire sufficient knowledge, understanding, skills and professionalism that underpin the education and training of health professionals. They should be aware of the current approaches used in health care and research. They are encouraged to integrate the knowledge of various key disciplines to further understand their respective fields. These objectives can be achieved by incorporating professional standards within the programme.